Field report on the Ogaden breed of cattle maintained at Alemaya University - Ermias, E. (2001)
Live weight and linear body measurements (wither height, body length and heart girth) of 133 Ogaden cattle, maintained at Alemaya University, were taken from July 24 to July 28, 2001. Weighing was done using weighing bridge of the farm in the morning before the animals went out for grazing. A textile measuring tape was used to measure linear measurements. Most nimals were in a good condition during the measurement, possibly due to the good grass growth of the season. Age of the animals was calculated as a difference between measurement date and the recorded birth date. For those without birth date records, dentition was used to classify into four convenient age groups, which had average ages of 64.3, 37.2, 20.4 and 1.2 months for females and 38.0, 37.4, 20.5 and 0.12 months, for males, respectively. Mature females measured 280.5kg for body weight, 161.4 cm for heart girth, 116.4 cm for height at withers and 141.0 for body length. Similarly males measured 321.0 kg for live weight, 161.3 cm for heart girth, 118.0 cm for height at withers and 141.5 cm for body length. The coat colour of this herd is uniform plain white. However, some animals have shades of black around the face, hump and rump. Hump is thoracic in location, large and prominent in both sexes, but larger in males. Most of the animals are polled, but when present, it is short and thick. The head profile is flat and the back line is straight. Lactation is not recorded from the herd, but a recent milk off-take measurement using a weigh-suckle-weigh method showed a range of 1 to 6 litres per cow per day. However, it is known that herd owners in the traditional Ogaden area mainly keep these cattle for their milk.